Legal consumer protection – with regards to the rights of hotel services users - Нина Максимовић; Рада Милићевић (Mенаџмент у хотелијерству и туризму, 2015)
The service user (consumer), in terms of Consumer Protection Act of the Republic of Serbia of 2011. Art. 5, Par. 1, is an individual who obtains services in the market for the purposes other than intended for his business, or other commercial activities. Nowadays a consumer is the focal point of any business. The existence of a business primarily depends on satisfaction but, more and more, on loyalty of consumers as well. Not infrequently in the literature can we encounter views that the consumer is actually the one who explains success, or failure, of some company.  The consumer is both a purpose and goal of any business, including the hotel one, but in practice individual service users do not gain such an impression. The author will try to point out the rights the hotel services users enjoy and how they can protect themselves from increasingly aggressive hotel companies marketing campaigns. In this regard, a range of activities primarily designed to protect consumers from unlawful business practices that violate his fundamental rights as a consumer are considered. In addition, we will point to the normative framework of consumer protection in the Republic of Serbia, at the same time discussing the advantages and disadvantages of the CPA implementation.